Analysis of Social Media and AI Application Use on Students' English Language Ability: A Meta-Analysis - Meydhisa Adelia Putri; Muhammad Mujahiddin Bakhir; Raihan Fahmi (INTEGRASI : Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the influence of social media and artificial intelligence (AI) applications on students' English language skills through a meta-analysis approach. The development of digital technology has changed the way students learn English, not only through formal classroom learning but also through digital platforms frequently used in everyday life. Social media and AI applications are two technologies widely used to support the English language learning process, particularly in the aspects of listening, speaking, reading, writing, vocabulary, and grammar. The research method used is meta-analysis by reviewing various relevant scientific articles from previous studies. Data were obtained through documentary studies from national and international journals, then analyzed descriptively and comparatively to find general patterns from the research results. The results of the study indicate that social media has a positive impact, especially in increasing exposure to authentic language, vocabulary mastery, and listening and speaking skills. Meanwhile, AI applications are more effective in supporting grammar, writing, and independent learning skills through instant feedback.